using Nd Isotopes 156-148 symmetry shapes for Transitions Studying ofinteracting boson model - Heiyam Najy Hady; Sami Eedan Abd (Al-Qadisiyah Journal of Pure Science, 2017)
The symmetry states structure of even -even 148-156Nd isotopes has been studied using the interacting boson model (IBM-1) .The energy levels , the electromagnetic transitions probability B(E2) and potential energy surfaces are analyzed which reveal the detailed nature of nuclei.In this chain 148Nd nucleus have a transition characteristic between vibrational limit SU(5)& γ- unstable limits O(6) .Different behavior shown by 150 Nd nuclei where the quadrupole – quadrupole interactions between bosons and the pairing forces were dominated while the studied structure band of nuclei 152-156Nd looks as distorted nuclei.The predicted theoretical calculations were compared with the experimental data in respective figures and tables ,it was seen that the predicted results are in a good agreement with the experimental data.In the framework of IBM calculations (46) new energy levels were determined for even -even 148-156Nd isotopes .This investigation increases the theoretical Knowledge of all isotopes with respect to energy levels ,reduced transition probabilities and potential energy surfaces.